IVth grade pupils’ mathematics learning outcomes influencing factors - Gesevičienė, Vilma; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2013)
The article deals the interface between the IVth grade pupil’s achievement in mathematics and elementary school teachers’ professional competence.